Pengembangan Sistem Navigasi Robot Beroda menggunakan Lokalisasi berbasis RFID dengan Pathfinding Algoritma A Star pada Simulasi Lingkungan Gudang - Farras Nabil; Dahnial Syauqy; Eko Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The rise of the use of E-Commerce sites places a huge burden on the logistical side, therefore many E-commerce companies implemented a fulfillment service in the form of warehousing that reduces the burden on the logistical side. The problem with these fulfillment services is the physical burden put on the workers of the warehouse. Therefore a system will be made that will help the worker with the use of a robot that can move from place to place automatically. This system will be in the form of a robot using a differential drive method and equipped with an RFID sensor to know it's location. An RFID will be placed in certain spots and will be named node. The system will use the A* algorithm to find a route starting from 0,0. The accuracy of the whole of the system is 75% for the movement of the robot, and 100% for the algorithm itself with a speed of computation between 34 and 199 microsecond for computing the path using A* in a map of size 4x3.